If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9)24=6(-x-3)
We move all terms to the left:
9)24-(6(-x-3))=0
We add all the numbers together, and all the variables
9)24-(6(-1x-3))=0
| 4(b−6)+194(b−6)+19= | | 13x+32-11x=-32-6x | | 9.18/0.08=x | | 10+(28+b)+15(5)=495 | | 0.04(10000)+0.08x=0.078(10000x) | | -0.88x^2-1.9x+1=0 | | X(4x-3)=63 | | 7-6x+11=5x+18-11x | | 1+a+15=37 | | 5(x-2)+14=3(x+12) | | 8x-50+(3x+10)=180 | | 13t+25=41,9 | | 2x+8+x=2x+15= | | 6(10-3x)=-120 | | 3x+3/3=5x | | 5m-12,7=13,8 | | 3x+3=5x*3 | | 9(j−84)=90 | | x2+x=90 | | -17c-10=-7c+20 | | 24(2x+6)=6(4x+36) | | p+116=7 | | x2+x3+x=90 | | 3x+6-8x=20-5x | | 5z-46=114 | | 8)-3(4r-8)=-36 | | 6k+5=41 | | -15(x-3)=-120 | | -8=w/2+2 | | 2g+5=-9 | | 10(v+6)=9 | | j2+ 13=16 |